Adequação do currículo do curso de pedagogia: habilitação em administração escolar e orientação educacional: ao mercado de trabalho - Cruz, Helena Soares da (1980)
The objective of this research is to study the curriculum of the Pedagogy Course (specialization in School Administration and Educational Orientation) at the College of Education of the Universidade do Amazonas. An effort was also made to examine the relation which exists between the formation received and the resultant practice developed in the primary and secondary schools of the city of Manaus. The study is composed of two phases: Initially, the importance of the study is discussed, together with an apresentation of the hypotheses and theoretica1 framework. This part of the study takes into consideration the roles of the School Administrator and Educational Orientator as specialists, giving special attention to the theoretical implications and legal aspects. The second part of the study consists of a field research, in which three instruments are uti1ized to span the following areas of education: course evaluation, methodology, supervised training, achievement evaluation, social reality and working conditions. The population studied consists of 80 educators occupying the functions of Directors, School Administrators and Educational Orientator’s. The results obtained reveal a large gap between the formation which the College offers and the working conditions of the professionals studied. The school administrators, playing the roles of assessors, are executing duties which do not require university training; the educational orientadors do not count with conditions for effective work, and, specially those conditions previewed by the theoretical authors of educational orientation. The professionals studied indicate as the chief strangling point of their work the great distance between 'theory and practice' taught in the university course. The professionals studied who operate as educational orientators portrayed a more critical vision with respect to the formation received. This studt suggests, as a form of conclusion, researches which could widen the knowledge scope of the educational reality analyzed.